Nanostructured templates for critical current density enhancement in YBa2Cu3O7–x films. (20th July 2020) - Armenio, A Angrisani; Piperno, L; Petrisor, T; Vannozzi, A; Pinto, V; Rizzo, F; Augieri, A; Mancini, A; Rufoloni, A; Mos, R B; Ciontea, L; Petrisor, T; et al.
Abstract: YBa2 Cu3 O7–x (YBCO) films grown by metal-organic decomposition (MOD) are promising candidates for the production of high performance high temperature superconductors (HTS) tapes. Moreover, artificial pinning centers (APCs) introduction proved to be a powerful tool for the improvement of transport properties in YBCO films. Along with the widely employed pinning strategies, such as the introduction of secondary phases in the YBCO matrix, a less studied approach is the nanostructuring of the YBCO substrate, in order to hinder its growth and to obtain a highly defective superconductive layer. In this work, oxide nanostructures were deposited on crystalline substrates via polymer assisted deposition (PAD), a low cost, highly versatile technique, so as to create nanoparticles that could interfere with epitaxial growth of chemical YBCO films. Preliminary analyses of the superconducting films grown on BaZrO3 (BZO) and ZrO2 (ZO) nanostructures showed that the decorated templates are highly effective in straining the YBCO matrix, leading to a significant improvement in transport properties. In fact, we obtain an increase of the critical current density, at 77 K, for YBCO grown on BZO and ZO decorated substrate of the order of 3 times at 2 T and even of the order of 8 times at 5 T with respect to the YBCO grown on bare substrate. The improvement of the pinning properties can be related to the intrinsic modification of the crystal structure of YBCO film due to the presence of these nanoparticles, in agreement with transmission electron microscopy (TEM) analysis performed.